Ramanuja - Edited by Anant Pai (Mumbai; Amar Chitra Katha, 2023)
Ramanuja (AD 1017-1137) lived for 120 years, traversing the land from Tamil Nadu to Kashmir. People flocked to him to understand his unusual message, the path to ultimate bliss. High caste or low, wealthy or poor, Ramanuja turned no one away. The great Acharya who wrote scholarly commentaries on sacred texts like the Bhagavad Gita was first and foremost a simple-hearted devotee. He inspired the Bhakti movement that spread throughout the country.
Keywords: Visionaries; Biography- Ramanuja (AD 1017-1137)